2006
DOI: 10.1007/s00330-005-0128-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CT densitometry with a slice thickness of 0.5 mm and audiometry in otosclerosis

Abstract: The appropriate cutoff Hounsfield unit (HU) value for the diagnosis of otosclerosis was determined and the correlation between the bone conduction threshold and the findings of computed tomography (CT) densitometry investigated. CT images, 0.5-mm thick, were evaluated in 24 ears with otosclerosis and 19 control ears. Eight regions of interest were set around the otic capsule. The mean HU values in the area anterior to the oval window (A-OW) and anterior to the internal auditory canal (A-IAC) were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 25 publications
3
42
1
1
Order By: Relevance
“…This result does not agree with Kawase et al [22] , who found a significant correlation between the density in the area anterior to the oval window and hearing thresholds (both AC and BC).…”
Section: Discussioncontrasting
confidence: 92%
“…This result does not agree with Kawase et al [22] , who found a significant correlation between the density in the area anterior to the oval window and hearing thresholds (both AC and BC).…”
Section: Discussioncontrasting
confidence: 92%
“…Certainly, the utility of CT bone attenuation measurement in the diagnosis of otosclerosis has been investigated, with some but not all groups showing focal diminished bone attenuation in patients with otosclerosis compared with controls. [8][9][10][11] Change in bone attenuation with age in the inner ear is of great interest to the authors and is currently under investigation by our group. Alternatively, we conjecture that the condition may be the cumulative result of repetitive microtrauma, which would increase in number throughout the course of life, but this is yet to be proved.…”
Section: Figmentioning
confidence: 99%
“…8 The attenuation degradation can be compared with the process that is visible in otosclerosis, where attenuated (D1) cortical bone of the otic pit is transformed into porous cortical bone containing more fibrous and less calcified tissue. 9,10 There is not yet a definite explanation why some particular areas are involved and others not. Given the fact that only the craniofacial area is involved, there must be a local factor that causes bone metabolic disturbance.…”
Section: Discussionmentioning
confidence: 99%